Structured computer organization - Tanenbuam, Andrew S. (New Jersey, 2002)
The first three editions of this book were based on the idea that a computer can be regarded as a hierarchy of levels, each one performing some well-defined function. This fundamental concept is as valid today as it was when the first edi-tion came out, so it has been retained as the basis for the fourth edition. As in the first three editions, the digital logic level, the microarchitecture level, the instruc-tion set architecture level, the operating system machine level, and the assembly language level are all discussed in detail (although we have changed some of the names to reflect modern practice).
Keywords: Computer architecture; Computer systems orgnization